To Study the Motivating Reasons Behind Performance of Sales Team: Exploring the Impact of Sales Staff Motivation on Organizational Performance (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This research investigates the factors involved in sales staff motivation in business organizations. The research study will entail the overall concept of sales staff motivation, whereby the influencing factors will be explicitly explored. In addition, the extent of sales staff motivation on organizational performance will also be analyzed.